Identifikasi Faktor-Faktor Penyebab Kesulitan Belajar Fisika dalam Materi Usaha dan Energi pada Siswa SMA - Aprianto Malotong; Syamsuriwal Syamsuriwal; Muhammad Zaky (Universitas Tadulako, 2022)
This research aimed to identify the learning difficulties experienced by students in class XI IPA at SMA Negeri 1 Nuhon in learning the physics topic of work and energy. The research method used was descriptive research with a qualitative approach. The research subjects consisted of six students who were selected based on recommendations from the physics teacher. Data was collected through test questions and analyzed using the stages of the Polya method, namely understanding the problem, planning a solution, implementing the plan, and reviewing it. Additionally, interviews were conducted to support the research. The results showed that students faced difficulties mainly in aspect II (planning problem solving), as most students were unable to write a plan for solving problems, such as outlining the steps and the correct formulas. Difficulties also arose in aspect III (solving problems), where all students struggled to complete and accurately record the correct answers. However, they demonstrated an ability to understand and complete questions one and two well and provide correct answers. Regarding aspect IV (revisiting), students often neglected to double-check and review their work, which resulted in errors. In conclusion, it can be inferred that students experienced difficulties in aspects II, III, and IV.